Effect of Transfer Temperature of Epididymis on Survival Rate of Semen and B6D2F1 Mice Developmental Capacity - Dan-Bi Lee; Kee Sang Park; Byoung Boo Seo (The Korean Society of Animal Reproduction and Biotechnology, 2016)
This study was conducted to evaluate the effect of transfer temperature of epididymis on survival rate of semen and development ability of B6D2F1 mice embryos. No significant differences were noted in the survival rate of semen (59.0% ± 0.1 vs. 47.6% ± 0.1), in vitro fertilization rate (90.7% ± 0.1 vs. 90.7% ± 0.1), developmental rate (90.0% ± 0.1 vs. 90.0% ± 0.1), and blastocysts formation rate (53.1% ± 0.2 vs. 52.3% ± 0.2) between groups. (NS; P>0.05). However, the zona hatched rate was significantly higher in the 4°C group compared to those of the 37°C group (47.8% ± 0.1 vs. 25.6% ± 0.2; p<0.05). When it comes to cell numbers of blastocysts, the % ICM (/total cells) was significantly higher in the group of 4°C compared to the 37°C (27.0% ± 0.1 vs. 18.3% ± 0.1; p<0.05). However there were no differences in total cell numbers (72.7 ± 31.6 vs. 62.0 ± 36.6), ICM cell numbers (17.0 ± 7.8 vs. 14.6 ± 8.6), TE cell numbers (55.8 ± 29.8 vs. 64.0 ± 24.4), the ratio of ICM:TE (1:4.2 ± 4.1 vs. 1:6.4 ± 7.2) between two groups (NS; P>0.05). Taken altogether, it is expected to achieve the best developmental ability of B6D2F1 mice embryos in the transfer temperature of epididymis. Also these results can provide fundamental data to maximize culture condition for in vitro fertilization on B6D2F1 mice. In future, therefore, it is expected that results herein might be applied for in vitro culture of human embryos.